ANALISIS PEMANGKU KEPENTINGAN (STAKEHOLDER) TERHADAP PENGELOLAAN SUMBERDAYA AIR DAS WAE BATU MERAH KOTA AMBON - Haulussy, Rizky; Latuamury, Bokiraiya; Iskar, Iskar (Universitas Pattimura, 2024)
This study aims to identify the main roles and tasks of relevant stakeholders in managing water resources and analyze the stakeholders influence and interests in managing water resources of the Wae Batu Merah Watershed of Ambon City. The research method uses a descriptive with a qualitative approach. The sampling method was purposive sampling, which in this research was 13 agencies/institutions/Apparatus Organizations (OPD). The research identified relevant stakeholders main roles and tasks in the management of water resources of the Wae Batu Merah Watershed in Ambon City including 13 Regional OPD/ agencies/ government/institutions. The results of mapping the influence and interests of stakeholders related to water resources management in the Batu Merah watershed show that there are four stakeholders in quadrant I (subjects), namely the Soya State Government, Batu Merah State Government, PT Dream Sukses Arindo and PDAM Kota Ambon. Quadrant II (Player) are the River Basin Center of Maluku Province, the Maluku Provincial Forestry Service. The Maluku Provincial Watershed Management Center, and the Disaster Management Agency of Ambon City. Quadrant III (Crowd) are the Maluku Provincial Watershed Forum, and the Regional Technical Implementation Unit Forest Management Unit of Ambon City. Finally, quadrant IV (context setters), are the Research and Development Agency of Ambon City, the Regional Development Planning Agency of Maluku Province, and the Environment Office of Maluku Province.